(3GdJMdjd Gdcej GdGbJUGOj (B:s (3GdYdGbGJ GdNWjI (B/s - (3GdcQNj, eLjOs ((3YeGf(B: s (3OGQ GdefGgL(B, s, 2010)
(3GfhGY GdGYOGO , NGUjI GdGJUGd aj GdGYOGO GdMbjbjI , GdGMOGKjGJ GdfJYGeOI , GdeJZjQGJ h GdKhGHJ , GdYdGbGJ h GdNW GdeSJbje , HYV GdYdGbGJ GdGbJUGOjI GdNWjI , GdeUahaGJ GdLHQjI , JMdjd GdeSJNOe ` GdefJL , GdHQeLI GdNWjI , GSJNOGe GdHQeLjI GdNWjI aj JNWjW Ch GJNGP GdbQGQGJ , eYGdLI NGUI aj GdHQeLI GdNWjI (B.s
Keywords: (3GdEMUGA GdJMdjdjs; (3GdEbJUGO GdJMdjdjs